2020
DOI: 10.1308/rcsann.2020.0069
|View full text |Cite
|
Sign up to set email alerts
|

Laser depilation as adjuvant therapy in prevention of recurrence of pilonidal sinus disease: initial experience of a district general hospital in the UK

Abstract: Introduction Pilonidal disease is a chronic condition involving the sacrococcygeal area. It can have a significant impact on quality of life, social activities and occupation. Surgery is the mainstay of treatment. However, laser depilation has been proposed as an adjunct to surgery and has shown improved results in some studies. We present our experience of laser depilation in the treatment of pilonidal disease in a district general hospital setting in the UK. Materials and methods A prospectively maintained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Several studies have suggested that laser hair removal helps to decrease risk of disease recurrence and should be considered as an adjunct therapy to the surgical treatment to minimize the disease recurrence. 31 , 32 Pronk et al conducted a systematic review of 14 studies to evaluate the effect of hair removal methods on recurrence rate and showed a recurrence rate of 9.3% in patients treated with laser hair removal compared to no hair removal (19.7%) and razor and cream depilation (23.4%). 30 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that laser hair removal helps to decrease risk of disease recurrence and should be considered as an adjunct therapy to the surgical treatment to minimize the disease recurrence. 31 , 32 Pronk et al conducted a systematic review of 14 studies to evaluate the effect of hair removal methods on recurrence rate and showed a recurrence rate of 9.3% in patients treated with laser hair removal compared to no hair removal (19.7%) and razor and cream depilation (23.4%). 30 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two patients in the surgery alone control group had abnormal healing or persistent sinusitis versus none who underwent a laser procedure after surgery 36 . Laser depilation was found to be a safe and effective adjunct to surgery in minimizing the recurrence of pilonidal disease 37 …”
Section: Part 1: Non鈥恠urgical Proceduresmentioning
confidence: 93%
“…36 Laser depilation was found to be a safe and effective adjunct to surgery in minimizing the recurrence of pilonidal disease. 37 Variable outcomes in laser hair removal depend on patient factors (e.g. FPT, hair colour, thickness and density, hormonal status) and the laser system used (e.g.…”
Section: Laser Tattoo Removalmentioning
confidence: 99%
“…Previously, standard treatment was excision of all the inflamed tissue allowing the wound to heal by granulation, although this can be a very long, tedious process. More recently, treatments are becoming less invasive [17]. If a pilonidal sinus is small, then it may only require antibiotic treatment.…”
Section: Specific Treatment Of Pilonidal Sinusmentioning
confidence: 99%